Single top quark at future hadron colliders: Complete signal and background study - Belyaev, A. S. [UNESP] (1999)
We perform a detailed theoretical study including decays and jet fragmentation of all the important modes of single top quark production and all the basic background processes at the upgraded Fermilab Tevatron and CERN LHC colliders. Special attention is paid to the complete tree level calculation of the QCD fake background which was not considered in previous studies. An analysis of the various kinematical distributions for the signal and backgrounds allow us to work out a set of cuts for an efficient background suppression and extraction of the signal. It is shown that the signal to background ratio after optimized cuts could reach about 0.4 at the Tevatron and 1 at the LHC. The remaining after cuts signal rate at the LHC for the lepton+jets signature is expected to be about 6.1 pb and will be enough to study single top quark physics even during LHC operation at a low luminosity. ©1999 The American Physical Society.